2018
DOI: 10.1186/s40478-018-0565-6
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of tau in nucleolar transcription and the stress response

Abstract: Tau is known for its pathological role in neurodegenerative diseases, including Alzheimer’s disease (AD) and other tauopathies. Tau is found in many subcellular compartments such as the cytosol and the nucleus. Although its normal role in microtubule binding is well established, its nuclear role is still unclear. Here, we reveal that tau localises to the nucleolus in undifferentiated and differentiated neuroblastoma cells (SHSY5Y), where it associates with TIP5, a key player in heterochromatin stability and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 42 publications
1
90
0
Order By: Relevance
“…Our results further support the emerging hypothesis that tau affects components of the translational machinery and that this regulation is altered in disease (Li & Götz, ). Tau has been shown to interact with several components of the translational machinery, including nuclear, ribosomal and RNA‐binding proteins (Meier et al , ; Vanderweyde et al , ; Maina et al , ). We have previously demonstrated that amyloid‐β induces increased de novo synthesis of tau through an activation of a signalling cascade that involves the Src kinase Fyn, the serine/threonine‐directed kinase ERK and the ribosomal protein S6 (Li & Götz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results further support the emerging hypothesis that tau affects components of the translational machinery and that this regulation is altered in disease (Li & Götz, ). Tau has been shown to interact with several components of the translational machinery, including nuclear, ribosomal and RNA‐binding proteins (Meier et al , ; Vanderweyde et al , ; Maina et al , ). We have previously demonstrated that amyloid‐β induces increased de novo synthesis of tau through an activation of a signalling cascade that involves the Src kinase Fyn, the serine/threonine‐directed kinase ERK and the ribosomal protein S6 (Li & Götz, ).…”
Section: Discussionmentioning
confidence: 99%
“…This seems to suggest that the protein synthesis machinery becomes altered before the onset of AD and this progresses with the disease process. Interestingly, tau has been shown to play a role in the nucleus and nucleolus as well as being a microtubule binding protein in the cytosol ( Maina et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA binding of Tau takes place at both genic and intergenic regions (Benhelli-Mokrani et al, 2018) and results in modulation of gene expression (Siano et al, 2019). Interestingly, nuclear Tau has also been involved in nucleolar transcription (Maina et al, 2018) and the decrease in nuclear Tau (detected with Tau-100 antibody) that takes place in AD CA1 and dentate gyrus neurons along disease progression might be pathogenic by leading to decreased protein synthesis (Hernández-Ortega et al, 2016). Finally, different mutations that alter the proportion of Tau isoforms as well as post-translational modifications can modify the affinity of Tau for microtubules.…”
Section: Functions Of Taumentioning
confidence: 99%